Multi-Span Steel–Concrete Bridges With Anti-seismic Devices: A Case Study - Pucinotti, Raffaele; Fiordaliso, Giovanni (Frontiers in Built Environment, 2019)
Seismic protection of structures in general, and bridges in particular, is very complex. In particular, the analysis of bridges with fluid viscous dampers and shock transmitting devices must be done on the best possible analytical model. Indeed a large number of factors must be treated accurately in order to be even more efficient in preserving human life. For complex structures, as is the case of the viaduct under examination, which contains numerous devices, consistent of fluid-viscous dampers and shock transmitters integrated with bearings, design assisted by testing is an almost necessary procedure. In this respect, the FE modelling of the viaduct have required a model updating procedure for its optimization. In fact, the viaducts built within the "Caltagirone Project", can be fully defined as works of great interest due both to the construction methods adopted and to the techniques of stress control in the seismic stage. The design process allowed to solve seismic issues deriving from structural irregularities (altimetric and planimetric) as well as from the high seismicity of the area. The analyses have been carried out by a Capacity Design approach, using non-linear seismic dissipative devices integrated to supports and checking that the substructures maintain substantially elastic. For this reason the piers have been modelled upon their non-linear behaviour under Takeda's hysteretic model. Furthermore, fluid viscous dampers and shock transmitters integrated with bearings, have been designed in accordance with the different stiffness by the substructures, this allowing to limit and partially dissipating stresses induced by earthquakes, in order to keep the deck and the substructures substantially elastic for Life-Safety Limit state condition (at the Ultimate Limit State). The verifications carried out have demonstrated the capability of structures to withstand the stresses under the Collapse Limit State condition without damage, plus ensuring the curvature capability by piers. The comparisons between experimental and numerical results together with the demanding qualification tests carried out in this study, demonstrates that the hydraulic devices are an efficient solution to control the seismic stresses induced on the viaduct and in its substructures, confirming the reliability of the aforesaid devices, that ensure a better structural safety.